Cardinalidad, ejemplo 1 - Chavarría-Molina, Jeffry (My University, 2018)
En este vídeo se presenta un primer ejemplo de cálculo de cardinalidades sobre conjuntos, dados condiciones sobre las cardinalidades de éstos y algunas de sus operaciones.

This video presents a first example of calculation of cardinalities on sets, given conditions on their cardinalities and some of their operations.
Keywords: Cálculo; Calculus; Operaciones matemáticas; Conjuntos; Mathematical operations; Sets; Matemáticas discretas; Discrete mathematics